Exploring a low SME equity equilibrium in Wales. Issue 10 (3rd October 2021) - Kapitsinis, Nikos; Munday, Max; Roberts, Annette
ABSTRACT: Previous research has examined geographical variations in SME access to external finance, especially bank loans. Rather less attention has been paid to how far SME equity access difficulties in more peripheral regions, and cities within these regions, is a demand or supply side issue, and how far equity investments are concentrated in specific urban areas in peripheral regions. This paper examines these topics through an analysis of small firm equity deals across the UK regions, before focusing on the case of the Welsh economy. In the case analysis a low equilibrium for small business equity investment in Wales is identified, with low demand and poor supply of equity, but with a relatively high concentration of equity deals in the Cardiff urban area. The paper examines the potential implications of a low equity equilibrium and provides a challenge for further research in the area.